Joint recommendations on cost calculation and estimation in paediatric clinical trials - Ahne, Gabriele; Nagel, Julia; Franz, Axel R.; Neubert, Antje; Schachtrup, Kristina; Helms, Simone; Klammt, Sebastian; Schwab, Matthias (GMS German Medical Science, 2024)
The conduct of clinical trials in paediatrics is essential to improve drug therapy in children. In Europe, paediatric clinical trials have been sup-ported by the European Paediatric Regulation since 2007, but there is still a great need for high-quality clinical trials. The personnel and time required to conduct clinical trials in accordance with EU Regulations 536/2014 and 745/2017 is considerably higher compared to other studies, such as observational studies. It is important that this additional workload for the trial centre is fully compensated, also taking into account EU state aid rules. In paediatric trials, it is necessary to take into account the special requirements of paediatric and adolescent medicine when calculating the additional costs. Within the framework of the pan-European paediatric study network c4c/GermanNetPaeT, a working group dealt with specific aspects of cost calculation in order to support paediatric study centres in internal cost calculation as well as in the subsequent preparation of financing requirements for industrial sponsors or public funders. In several workshops the working group developed a cost calculation template with the content derived from the “Joint recommendations for a total services account as a factor in simplifying contracts” of the Deutsche Hochschulmedizin (DHM, German University Medicine), the Netzwerk der Koordinierungszentren für Klinische Studien (KKS Network, Network of Coordinating Centres for Clinical Trials) and the Verband Forschender Arzneimittelhersteller (vfa, German Association of ResearchBased Pharmaceutical Companies). By estimating the specific time required for measures and investigations as part of a sample study, the background to the increased time required was discussed and a list with aspects to be considered for cost calculation was compiled together with the study centres. The paediatrics-specific aspects mentioned in detail are intended to increase understanding of the particular problem of higher costs for clinical trials involving children and adolescents and the need for correspondingly appropriate remuneration. This transparent and comprehensible presentation of the higher financial requirements for both the study centres and the financial supporters is intended to promote the high-quality conduct of clinical trials in paediatric study centres in the long term.
CRIS-Team Scopus Importer:2024-05-31
Keywords: clinical trial; cost calculation; paediatrics